For better or for worse: the impact of EPAs on Africa's regional integration - Moleli, Moretlo (Department of Political Studies, 2022)
Regional Economic Communities (RECs) in Africa are often plagued with disorientation and sub-par trade relations. It is well-established that extra-continental trade partnerships between Africa and the West have resulted in the delaying of industrialisation and the subsequent growth in intra-continental and intra-regional trade. This study aims to determine whether the Economic Partnership Agreements (EPAs), engineered by the European Union (EU) between Africa and the EU have been beneficial to Africa's quest for regional economic integration. This was done through qualitative research. The theoretical perspective of Neofunctionalism is used in order to explore how scholars perceive regional integration. This is accompanied by some conceptual lenses stemming from the umbrella of New Regionalism theory, particular these are: Open Regionalism, The WIDER Approach, Regionalism from Below (New Regionalisms), as well as the External Guarantors Model. The study showed that the trade and economic agreements the EU established with Africa have been asymmetrical and have left Africa as a producer of raw materials. Thus, while the EPAs may produce some positive outcomes for Africa, the costs far outweigh the benefits. The EPAs have the potential to negatively affect Africa's quest to establish a thriving African Continental Free Trade Area (AfCFTA). In this regard, the EPAs are detrimental to, rather than enhancing Africa's regional integration efforts. Africa's regional economic communities (RECs) are critical to the success of the AfCFTA. Future trade agreements between Africa and the EU should therefore be crafted in ways that enhance Africa's regionalism.